Must we defend Nazis?: Hate speech, pornography, and the new First Amendment - Delgado, Richard (New York University Press, 1997)
The opening salvo : naming the harm. Words that wound : how racist hate speech harms the victim. Law's earliest responses -- Pornography and harm to women : how even social scientists have sometimes failed to see the need for relief -- The assault on the citadel : legal realism shakes up orthodoxy. First Amendment formalism is giving way to First Amendment legal realism -- Campus anti-racism rules : constitutional narratives in collision, or, why there are always two ways of looking at a speech controversy -- Images of the outsider : why the First Amendment marketplace cannot remedy systemic social ills. Social science and narrative theory are questioning faith in the freemarket of ideas -- Retreat to policy analysis : "even if what the crits say is so ..." Paternalistic arguments against hate-speech rules : pressure valves and bloodied chickens. The liberals' response to the crumbling of certainty -- The toughlove school : neoconservative arguments against hate- speech regulation. ("I just let it roll off my back") -- "But America wouldn't be America anymore" : the experience ofother countries shows that adopting hate-speech rules would not cause the skies to fall; America would be even more american -- "From where I sit" -- The special problems of judges and progressive lawyers. Hateful speech, loving communities : why judges are sometimes slower than others at seeing the need for reform -- "The speech we hate" : the romantic appeal of First Amendment absolutism. Does defending Nazis really strengthen the system of free speech?